The Role and Benefits of People's Requirements (MPRS) in The Indonesian State System after The 1945 Amendment: Optimization and Challenges - Soesatyo, Bambang; Suganda, Atma; Mau, Hedwig A (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The study seeks to examine the role and jurisdiction of the People's Assembly of Permusyavaratan (MPR) within the Indonesian statehood system after the modification of UUD 1945. It also intends to identify the efforts made to optimize its functioning and the problems encountered. Normative legal research methods are employed to specifically analyze primary, secondary, and tertiary legal material. The primary legal materials consist of the 1945 Basic Act and its subsequent changes, along with the relevant statutes that regulate the MPR. Secondary legal resources encompass pertinent literature, periodicals, and scientific publications. The research findings indicate that the modifications made to the 1945 UUD have limited the jurisdiction of the MPR, which currently possesses only one primary authority while the others are considered secondary. Constitutional Supremacy establishes the Constitution as the primary framework for governing the state, with the MPR being seen as an autonomous institution alongside the DPR and DPD. While the powers of the MP are restricted, responsibilities like the Socialization of the Four Pillars continue to be essential in maintaining the fundamental foundations of the state. The enhancement of the MPR's authority relies significantly on the agreement among parliament members as stated in the MD3 Act. The primary obstacle it faces is to ensure the MPR remains relevant and effective in a constantly changing statehood environment. The paper suggests implementing strategic initiatives to enhance the role of MPR in the Indonesian statehood system by implementing policy reforms and improving institutional capability.